2004
DOI: 10.1099/jmm.0.05378-0
|View full text |Cite
|
Sign up to set email alerts
|

Protection in a mouse peritonitis model mediated by iron-regulated outer-membrane protein of Salmonella typhi coupled to its Vi antigen

Abstract: Vi polysaccharide and iron-regulated outer-membrane proteins (IROMPs) were extracted and purified from the standard strain of Salmonella typhi, Ty2. These were then conjugated by chemical coupling using the carbodimide method. Vi-IROMP conjugate was tested for its ability to protect against colonization by S. typhi in different organs. Mice immunized with 2 . 5 ìg Vi-IROMP conjugate showed the most protection, as the least bacterial colonization of spleen, liver and Peyer's patches was observed. Peritoneal mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…The expression of three distinct bands in the molecular mass range from 66 to 97 kDa is in agreement with an earlier study (Fernandez-Beros et al, 1989) of IROMPs from the same strain (S. typhi Ty2). However, it differs from the profile shown recently by Chibber & Bhardwaj (2004) using the same strain. The dipyridyl used in that study may not have been efficient in causing the chelation of iron present in the medium.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The expression of three distinct bands in the molecular mass range from 66 to 97 kDa is in agreement with an earlier study (Fernandez-Beros et al, 1989) of IROMPs from the same strain (S. typhi Ty2). However, it differs from the profile shown recently by Chibber & Bhardwaj (2004) using the same strain. The dipyridyl used in that study may not have been efficient in causing the chelation of iron present in the medium.…”
contrasting
confidence: 99%
“…While evaluating any antigen for its vaccine potential, it is desirable to determine the minimum concentration of the antigen that gives a protective effect. It has been shown by Chibber & Bhardwaj (2004) that 50 ìg of IROMPs and 2 . 5 ìg of Vi-IROMPs conjugate of S. typhi gives protection in a mouse peritonitis model.…”
mentioning
confidence: 99%
“…It has been shown that the S. Typhi Vi capsular polysaccharide (Vi-CPS) subunit vaccine can prevent typhoid fever. A single intramuscular injection of this vaccine conferred about 65 and 72 % protection in South Africa and Nepal, respectively (Acharya et al, 1987;Klugman et al, 1987;Szu et al, 1994;Tang et al, 2003;Chibber & Bhardwaj, 2004). The Vi-CPS vaccine has now been licensed in .93 countries worldwide, although it is not commonly used as part of vaccination programmes in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Since anticapsular antibodies have been shown to be present and protective in clinical and experimental studies [26][27][28], surface-exposed capsular polysaccharide (CPS) of E. coli is therefore considered an important virulence determinant [4,29,30]. Since CPS alone is a T independent antigen, for better immunogenicity there is a need to couple it with carrier proteins to make it T dependent [31][32][33][34]. Over the years, different carrier proteins have been used for coupling by different workers [35].…”
Section: Discussionmentioning
confidence: 98%